Incumplimiento intencional del régimen de visitas frente al interés superior del niño en el cantón Echeandía, en el año 2021 - Garcia Aguirre, Dayana Brigith (2023)
The Constitution of the Republic of Ecuador (2008), in its Art. 44, enshrines the principle of the best interests of the child, which seeks their integral development, within their growth process, determining the obligation of the State, society and the family to generate the most appropriate conditions so that the rights of the minor prevail over those of any other person. Precisely, one way to ensure the integral development of the minor is through coexistence with his family in general and his parents in particular, including, if necessary, through the establishment of a system of visits to the parent, allowing In this way, the child satisfies his social, affective-emotional and cultural needs. In this context, in this document, the research topic is discussed from an analytical point of view on the intentional breach of the visitation regime by the parent who holds custody of the child, who prevents the minor from living with the parent at who has been set a regime of views, all this against the principle of the best interests of the child. Keywords: best interests of the child, visiting regime, non-compliance, intentional, comprehensive development.